2018
DOI: 10.1186/s13058-018-0951-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and genomic hallmarks of breast tumours developed by ATM deleterious variant carriers

Abstract: BackgroundThe ataxia telangiectasia mutated (ATM) gene is a moderate-risk breast cancer susceptibility gene; germline loss-of-function variants are found in up to 3% of hereditary breast and ovarian cancer (HBOC) families who undergo genetic testing. So far, no clear histopathological and molecular features of breast tumours occurring in ATM deleterious variant carriers have been described, but identification of an ATM-associated tumour signature may help in patient management.MethodsTo characterise hallmarks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 62 publications
(87 reference statements)
9
28
0
Order By: Relevance
“…Whereas tumors with germline pathogenic variants with LOH or AST were enriched among BRCAness high tumors, ATM BAL tumors showed low BRCAness probability and were not identified as the triple‐negative subtype (Table B). This finding is indeed consistent with previous observations, in which ATM ‐mutated breast cancers showed low COSMIC signature #3, 18 low HRD‐LST, 16 and a luminal subtype 28,40 . Although ATM is a component of the HR repair pathway, ATM loss of function could exert a distinct tumorigenic program that differs from that of the other HBOC‐HR genes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Whereas tumors with germline pathogenic variants with LOH or AST were enriched among BRCAness high tumors, ATM BAL tumors showed low BRCAness probability and were not identified as the triple‐negative subtype (Table B). This finding is indeed consistent with previous observations, in which ATM ‐mutated breast cancers showed low COSMIC signature #3, 18 low HRD‐LST, 16 and a luminal subtype 28,40 . Although ATM is a component of the HR repair pathway, ATM loss of function could exert a distinct tumorigenic program that differs from that of the other HBOC‐HR genes.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is indeed consistent with previous observations, in which ATM-mutated breast cancers showed low COSMIC signature #3, 18 low HRD-LST, 16 and a luminal subtype. 28,40 Although…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of both BRCA1 and BRCA2 alleles appears to be required for the HRD characteristic of BRCA-related HBOC [22]. Two-hit inactivation has also been described, in smaller case series, for PALB2-and ATM-related HBC, and BRIP1-related hereditary ovarian cancer [42][43][44].…”
Section: Discussionmentioning
confidence: 91%
“…In particular, families carrying heterozygous germ-line variants of ATM gene have a 5- to 9-fold risk of developing breast cancer, particularly in women younger than 50 years [ 6 ]. Approximately, 3% of the families affected by hereditary breast and ovarian cancer harbors a loss-of-function ATM mutation [ 7 ]. Recent studies identified ATM as the second most mutated gene after CHEK2 in BRCA-negative patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%